Statuten mittelalterlicher Ordensgemeinschaften: Strategien normativer Stabilisierung mittels statutarischer Gesetzgebung am Beispiel der Zisterzienser, Prämonstratenser, Dominikaner und Franziskaner - Bitterlich, Markus (Technische Universität Dresden, 2015)
Keywords: ⚖️ chapters and statutes; 📚 premonstratensian (general)

Die Statuten des Prämonstratenserordens von 1244/46 und ihre Überarbeitung im Jahr 1279 - Krings, Bruno (Analecta Praemonstratensia, 2007)
Keywords: ⚖️ chapters and statutes

Das Generalkapitel im hohen Mittelalter: Cisterzienser, Prämonstratenser, Kartäuser und Cluniazenser - Cygler, Florent (Vita regularis, 2002)
Keywords: ⚖️ chapters and statutes

Die ältesten Klostergesetzgebungen von Prémontré, Oigny, Cîteaux, Klosterrath und Arrouaise und ihre Beziehungen zueinander - Van De Perre, Dirk (Analecta Praemonstratensia, 2000)
The first chapter of this study is devoted chiefly to examining the relationship among the oldest monastic rules of Citeaux, Kloosterrade, Oigny and Prémontré, the examination showing that, for the chapters of those rules that are similar, there is line of dependence running from Citeaux to Prémontré to Oigny and from Kloosterrade to Prémontré to Oigny. This insight has also led to the conclusion that the oldest version of the Premonstratensian Rule is not the PW text and that a Px version must have existed of which the PW text is a later variant. Oigny did not copy the PW version, but rather a Px’ version, which is a hypothetical variant of Px. The second chapter goes into more detail about the reasons why, in the Premonstratensian Rule, the superior was called abbas (abbot) and the second in authority prepositus (provost). This is interpreted as a compromise between the German tradition, in which the superior was known as prepositus, and the French tradition, in which he was known as abbas. In the third chapter, lastly, an examination is made of the relationship among the rules of Prémontré, Citeaux and Arrouaise for lay brothers, and shows that the Rule of Prémontré was the oldest, a conclusion that is diametrically opposed to the recent position taken by C. Waddell that the Lay-brother Rule of Citeaux had already been drawn up around 1120 and was thus older than that of Prémontré. The examination also shows that, in its first edition, the Rule of Arrouaise adopted elements of the Premonstratensian Rule and was subsequently supplemented with elements from the oldest Lay-brother Rule of Citeaux and the later Rule of Prémontré.
Keywords: ⚖️ chapters and statutes

Das Ordensrecht der Prämonstratenser vom späten 12. Jahrhundert bis zum Jahr 1227. Der „Liber consuetudinum“ und die Dekrete des Generalkapitels - Krings, Bruno (Analecta Praemonstratensia, 1993)
Keywords: ⚖️ chapters and statutes

Die Triennal- und Annual kapitel der sächsischen Zirkarie des Prämonstratenserordens: Eine Einleitung zur beabsichtigten Edition Acta capitulorum triennalium et annalium circariae Saxoniae ordinis Praemonstratensis inde ab anno 1466 usque ad annum 1516 - Dolista, Karel (Analecta Praemonstratensia, 1974)
Keywords: ⚖️ chapters and statutes; 🇩🇪 germany (general)

Die Verfassung des Prämonstratenserordens und die Wandlungen im weltlichen Bereich - Lentze, Hans (Österreichisches Archiv für Kirchenrecht, 1959)
Keywords: ⚖️ chapters and statutes